PERPUTARAN MODAL KERJA DAN PERPUTARAN KAS UNTUK MENDORONG PROFITABILITAS PERUSAHAAN SEMEN - Septiawan, Agung; Yuliani, Yuliani; Raneo, Agung Putra; Mutia, Fida (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
The objective of this research is to examine how profitability in the Cement Industry, which is listed on the Indonesia Stock Exchange, is impacted by Working Capital Turnover and Cash Turnover. The study will focus on a sample of five publicly-traded cement companies as its research population. The method of sampling used in this study was purposive, meaning that the selection of the three companies was based on specific criteria. The method of sampling used in this study was purposive, meaning that the selection of the three companies was based on specific criteria. The data used were financial statements of cement industry companies that went public in Indonesia from December 31, 2005 – December 31, 2021. The data was processed using panel data regression. The study's findings indicate that the working capital turnover (WCT) does not have an impact on the return on assets (ROA), whereas the cash turnover (CT) has a significant influence on the return on assets (ROA). The implications of research is that return on assets (ROA) has the potential to be a very important indicator for companies in measuring their financial performance, and can provide significant benefits in improving the company’s financial performance and increasing investor confidence.